COMPETENCES OF TEACHERS IN TEACHING, SUPPORTED BY INTERACTIVE WHITEBOARDS TOUCH - SZOTKOWSKI, René (Trends in education, 2009)
The article deals with basic skills of teacher in teaching supported by interactive whiteboards touch. The main teacher's hardware and software competences form interconnected structure whose separate parts affect the final shape of teaching supported by interactive whiteboards touch.
Keywords: teacher; education; competences; touch interactive board; hardware; software.